Might Technology Undermine First-Person Authority? - Doyle, Casey (Erkenntnis, 2026)
The paper focuses on self-knowledge of attitudes like belief, desire, and intention. It motivates a constraint on when it is rational to treat a source as an authority. Then, drawing on the "transparency" of belief and other attitudes, it argues that the constraint is not satisfied in the case of knowing one's own mind by relying on AI or any other technology. Against some AI optimists, the paper argues that there are principled reasons why the task of knowing one's mind should not be outsourced to computers. Neither is AI a threat to the practice of deferring to avowing subjects.